The Impact of Stress and Parental Verbal Abuse on Early Childhood Emotional Development: Indonesia - Rahmadani, Efriza; Sumadi, Tjipto; Nurjannah, Nurjannah (Perkumpulan Pengelola Jurnal (PPJ) PAUD Indonesia, 2023)
Parents have an important role in stimulating aspects of early childhood emotional development, but when parents are experiencing stress parents often commit acts of verbal abuse against children. This study aims to determine the effect of stress and verbal abuse by parents on the emotional development of children aged 5-6 years. This research is an ex post facto study conducted in the city of Pagar Alam. The population of this study is children aged 5-6 years whose parents' conditions were affected by the Covid-19 pandemic. They will be taken from South Pagar Alam sub-district,. For the research sampling technique using random clusters from 11 Kindergartens, researchers took random samples to represent the research sample, namely as many as 3 Kindergartens. the object of the emotional development of the respondents was 183 children aged 5-6 years, and for stress and acts of verbal abuse the respondents were 183 parents whose children were respondents to the object of emotional development. The data collection technique in this study was observation, and used a questionnaire. The analysis technique in this study uses path analysis. Based on the results of the path analysis (Path Analysis) and the results of the research hypothesis test showed that stress and acts of verbal abuse have a negative effect on children's emotional development, while stress has a positive effect on acts of verbal abuse.